2022
DOI: 10.1093/police/paac059
|View full text |Cite
|
Sign up to set email alerts
|

Police ethics committees in England and Wales: Exploratory online and web surveys

Abstract: Drawing from practice and learning of Clinical Ethics Committees, Police Ethics Committees began to emerge in the years following the statutory creation of the College of Policing in 2012, but there is little research on their form and effectiveness. This paper reports the results of exploratory online and web surveys undertaken in 2021. The surveys revealed committees with the word ‘ethics’ in their title fell within two different types. First, discursive and advisory committees, largely inclusive but with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In the meantime, in the absence of training and advice other than the broader guidance offered by the CoP's vulnerability guidelines and the Code of Ethics, and having presented some of the considerations at play, we recommend that LEOs faced with a disclosure dilemma utilise the views of their force's ethics committee where this is available (recent research has found that 22 police force areas in England and Wales operate an ethics committee) (Snelling et al, 2022).…”
Section: An Ethically Appropriate Approach To the Disclosure Decisionmentioning
confidence: 99%
“…In the meantime, in the absence of training and advice other than the broader guidance offered by the CoP's vulnerability guidelines and the Code of Ethics, and having presented some of the considerations at play, we recommend that LEOs faced with a disclosure dilemma utilise the views of their force's ethics committee where this is available (recent research has found that 22 police force areas in England and Wales operate an ethics committee) (Snelling et al, 2022).…”
Section: An Ethically Appropriate Approach To the Disclosure Decisionmentioning
confidence: 99%
“…There is some evidence that ethical scrutiny of Big Data has been applied systematically in LEAs, after the interviewees first raised concerns, as evident from the above-mentioned Ethics Committee (WMPCC, 2019). It should be noted that this case is perhaps an outlier, as the author did not encounter similar cases at other LEAs in the UK, even though ethics committees have become standard practice at UK LEAs since 2012 (Snelling et al, 2022).…”
Section: Synthesis Of Dependent Variablesmentioning
confidence: 91%